Predation by young Cassis tuberosa (MollusCa: gastroPoda: Cassidae) on lytechinus variegatus (eChinoderMata: eChinoidea), under laboratory Conditions - Pequeno, Ana Paula Leite Cavalcante; Cascon, Helena Matthews (Arquivos de Ciências do Mar, 2010)
In this study we analyze the predatory behavior of young Cassis tuberosa on the sea urchin Lythechinus variegates by means of observations carried out on Redonda Beach, Icapuí, Ceará. Individuals of predator and prey were collected at low tide and were taken to the laboratory in aerated boxes. Each juvenile of C. tuberosa was placed together with one Lythechinus variegatus in a 50-liter tank. During the experiment the number of consumed prey was registered and the eaten individuals were replaced. This experiment lasted for one month at 26-28 o C and 35 of salinity and was replicated ten times. We registered the position and the dimensions of the bore holes on the sea urchins. The bore hole were complete, with 4 to 5 mm in diameter and had teeth marks of the radula on their edge. We found, in every prey, a dark spot around the predation holes, which was probably a reaction of the calcium carbonate test of the prey to the sulfuric acid from the predator. No statistical significant preference for oral or aboral sides was observed. The defense mechanism of the prey was based on behavioral strategies.